The level of academic ambition among university students in the light of some variables Field study at the Faculty of Education, Tishreen University - SBEIRA , FOUAD (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The objective of the research is to determine the level of academic ambition in a sample of the students of the Faculty of Education at Tishreen University, and to find the differences according to the gender variable (males and females), the differences according to the specialization of secondary certificate (literary-scientific) (72) a student from the Faculty of Education, was used descriptive approach, and was based on the scale of Salah al-Din Abu Nahia (1986). The research found the following results: There is anhigh level of academic ambition among students, and there are no statistically significant differences depending on the variables (gender, specialty, place of residence). The study suggests increasing attention to the positive variables of the personality and mental health of the university student, which will support them and achieve healthy psychological and social development, and supports the success and academic achievement of students at all levels of study. It also emphasizes the need for the university administration to take care of students and introduce them to the university and train them to solve various problems.